TGFs, Gamma‐Ray Glows, and Direct Lightning Strike Radiation Observed During a Single Flight of a Balloon‐Borne Gamma‐Ray Spectrometer - Christopher Helmerich; Todd McKinney; Everett Cavanaugh; Sarah Dangelo (Earth and Space Science, 2024)
Abstract Terrestrial gamma‐ray flashes (TGFs) and other high‐energy radiation phenomena related to thunderstorms remain incompletely understood since their discovery nearly 30 years ago. Space and ground‐based platforms have provided insights, but limitations exist in temporal resolution, signal‐to‐noise ratios, and proximity to events. This study presents findings from a balloon‐borne gamma‐ray spectrometer flown into a thunderstorm over northern Mississippi on 19 June 2023. The instrument detected three distinct millisecond‐duration TGF events correlated with lightning strikes. Sustained gamma‐ray glows lasting up to 2 minutes were measured and tied to thunderstorm electrostatic fields. Notably, radiation was observed during a direct lightning strike to the payload. This complex 800‐millisecond event reveals insights into radiation from leader propagation and return strokes. These findings from a single balloon flight demonstrate the prevalence of energetic processes within thunderstorms. Finally, the balloon platform offered an exceptional combination of temporal resolution and validation capabilities to advance the understanding of thunderstorm radiation motivating future follow‐up studies.